Estresse, coping, burnout, sintomas depressivos e hardiness entre discentes de enfermagem - Freitas, Etiane de Oliveira (2012)
It is a quantitative, exploratory and transversal research with aiming to analyze stress coping, burnout, depressive symptoms and hardiness in nursing students. The survey was conducted in a public university of the Rio Grande do Sul. Data collection was performed in April and May 2011. Was followed a research protocol that consists of Form sociodemographic and academic of the students, Instrument for Assessment Nursing Students Stress, Coping Strategies Inventory, Beck Depression Inventory, Maslach Burnout Inventory - Student Survey and Hardiness ScaleThe socio-demographic and academic variables, well as items that compose the instruments, were analyzed using the Statistical Analysis System program - version 9.1 and Statistica - version 7.1. Internal consistency of the scales was attested by Cronbach's alpha coefficient. The study population consisted of 130 nursing students, 86.92% female, 69.23% aged between 20 and 24 years, 86.92% single, 93.08% childless, 60% live with family, 70.77% don t practice sport, 68.46% use leisure activity, 64.62% participate in group research / study, 64.62% don t receive scholarships, 93.08% have no other work activity, 89, 23% report no professional experience in health field, 97.69% didn´t attend another college, 86.92 are satisfied with the course and 34.62% thought in give up it. The students have, an average, of 22.5 years. They are registered, on average, in 5.30 disciplines, take 37.57 minutes to arrive at university, studying on average 2.19 hours per day and dedicate 5.25 hours to the research group / study weekly. Among situations that represent the most stress, those relating to the time management were prevalent and situations about professional communication were assessed as less stressful. Regarding coping strategies, it was found that the factor problem solving demonstrated the highest average (1.72), therefore, was factor most used by students. The confrontation factor obtained the lowest average (0.78), so the least factor used by this population. With regard to the Burnout Syndrome, 51.54% of students have high emotional exhaustion, 53.85% low depersonalization and 52.31% highest professional effectiveness. It was identified 20.07% of students with burnout indications. In the assessment of depressive symptoms, was found that 76.92% people are within the normality, 16.92% with the presence of dysphoria and 6.15% with a picture suggestive of depression. In relation the hardiness personality, 51.54% and 54.62% of students are high in the commitment and control domains respectively and 50.77% are under in the challenge domain. It was identified 19.23% of students with hardy personality. Were found significant correlations among stress, coping, burnout, depressive symptoms and hardiness. It is concluded that hardiness personality interfere in the stress assessment , the use of coping strategies, the occurrence of burnout and depressive symptoms. The results of this study will can help nursing course coordinate in the curriculum evaluation, contribute with interventions in the daily academic in order to make it more productive and less stressful, as well as minimize the effects of stress and decrease the risk of burnout in nurses and recent graduates, and create opportunities to better health in nursing students and future professionals in entry into the world of work.